Assessing the Importance of Psychosocial Factors Associated With Sustainable Organizational Development During COVID-19 - Dragan, Florin; Luo, Chaoping; Ivascu, Larisa; Ali, Majid (Frontiers in Psychology, 2021)
Involvement in sustainable development is a voluntary activity. Organizations apply the principles of sustainable development only when they identify several benefits. These benefits are identified, especially with the financial ones. In the case of financial benefits, persons with decisional power are involved in organizational sustainability (SO). The involvement of organizations in SO has different levels of intensity. These intensity levels are influenced by psychosocial factors, attitudes towards organizational risks, and organizational and urban policies. The present paper identifies the key psychological factors involved in the application of SO principles within organizations. For this research, five groups were created for in-depth interviews with key people from Romania's innovative companies. The data obtained were analyzed with framework analyzes. To identify the importance of the framework analysis factors, the Delphi method was used, in which 20 experts from different fields of activity were involved. Following the rounds involved in the Delphi method, the ranking of psychosocial factors (PF) on four levels of importance was accepted, based on the theory of planned behavior and reasoned action theory. These levels were correlated with the intensity levels of involvement in sustainable development. The entire market study was conducted during Covid-19, which had a significant impact on certain directions. As a result, it could be observed that motivation, learning attitude, behavior, and intention to take precedence are essential in the SO approach.